The Exploratory Research on Mixed Refrigerants of A Five-Stage Autocascade Refrigeration System (Zhileng xuebao)
A five-stage Auto-cascade refrigeration cycle(ARC) is brought forward.According to the experiences that different systems with different components and proportion of mixed refrigerants can result in different evaporating temperature,the components selecting principle of non-azeotropic mixed-refrigerants is analyzed and the components are selected.The calculated methods of mixtures in ARC system is discussed.R22,R23,R14,R740 and R728 are selected as refrigerants in this system based on the requested conditio...